The anxiety of students on deduction level in proving the geometry theorem - Ni'mah, K; Susanto; Sunardi; Hobri (Journal of physics. Conference series, 2020)
This study aims to describe the anxiety of university students who were on deduction level in proving the geometry theorem. This was conducted to find out student anxiety, so that it can be handled and anticipated. Anxiety is the state of feeling students' uncomfortable, worried, and afraid. The type of this research is qualitative-descriptive. The subjects were taken as many as 3 students who were at the deduction level based on the Van Hiele geometry ability test. Data was collected through theorem proofing tests and interviews conducted after the test. The results of this study indicate that the symptoms of cognitive anxiety (uneasy, nervousness and confuse) occur when the subject begins to understand the problem in the theorem. Symptoms of physiological anxiety (sweating, body feels hot) and behavioral symptoms (physical tension, impatience) appeared when the subjects connected the elements of proof on theorem in geometry. The results of this study are expected to be used by students or lecturers, especially in learning to teach how to proof theorem in geometry.